Representasi Komunikasi Negosiasi dalam Film Drama Remaja - Fahira Ananda; Wiki Angga Wiksana (UNISBA Press, 2023)
Abstract. Film is considered to be a real mass media in the sense that it is able to reach a large and fast population. In the increasingly rapid development of technology, various media have been used to provide understanding or display the reality in people's lives regarding communication, namely by using films as a medium for delivering messages and negotiating in communication. This study discusses the representation of negotiation communication in the film Dear Nathan: Thank You Salma, where the content is the result of observing the scene and dialogue as the basic tools. The purpose of this study is to find out how the film Dear Nathan: Thank You Salma is based on the subject-object position and the position of the reader and to find out the representation of negotiation communication in the film Dear Nathan: Thank You Salma. The method used in this research is qualitative with Sara Mills' critical discourse analysis approach. The results of this study concluded that the position of the subject described in this film is Salma and Zanna but focuses on the character of Zanna. Then the representation of negotiation communication in the film begins when women are considered weak and unable to solve their own problems, this is where the negotiation communication occurs between players. Abstrak. Film dianggap menjadi media massa yang sesungguhnya dalam artian film mampu menjangkau populasi dalam jumlah yang banyak dan cepat. Dalam perkembangan teknologi yang semakin pesat, berbagai media telah digunakan untuk memberikan pemahaman atau menampilkan realitas dalam kehidupan masyarakat mengenai komunikasi, yakni dengan menggunakan film sebagai media penyampaian pesan serta bernegoisasi dalam komunikasi. Penelitian ini membahas mengenai representasi komunikasi negosiasi dalam film Dear Nathan: Thank You Salma, dimana isinya merupakan hasil dari mengamati scene dan dialog sebagai perangkat dasarnya. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana film Dear Nathan: Thank You Salma berdasarkan posisi subjek-objek dan posisi pembaca serta mengetahui representasi komunikasi negosiasi pada film Dear Nathan: Thank You Salma. Metode yang digunakan pada penelitian ini ialah kualitatif dengan pendekatan analisis wacana kritis Sara Mills. Hasil dari penelitian ini disimpulkan bahwa posisi subjek yang digambarkan dalam film ini adalah Salma dan Zanna akan tetapi berfokus pada karakter Zanna. Kemudian representasi komunikasi negosiasi dalam film tersebut bermula pada saat perempuan dianggap lemah dan tidak mampu untuk mengatasi masalahnya sendiri, dari sinilah terjadinya komunikasi negosiasi yang terjadi antar pemain.